PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR DI SMAN 1 SUNGAI KAKAP - Yepi Oktaviani; Bambang Genjik S; Okianna Okianna (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the effect of parents socioeconomic status on students learning motivation in economics class XI IIS at SMA N 1 Sungai Kakap. This study uses quantitative methods. Sources of data in this study were students of class XI IIS SMAN 1 Sungai Kakap with a sample of 64 people. Data collection techniques used consisted of questionnaires and documentation. The data obtained from the respondents questionnaire results were then tested for validity, reliability, analysis prerequisite test using normality test and linearity test, then hypothesis testing using simple regression analysis and t test. From the regression results obtained equation Y = 50.684+0.275 X. Hypothesis testing with t test obtained tcount 2.054 and ttable 1.998 which means t count > t table which means there is a positive and significant influence between the two variables and the results of the relationship between people's socioeconomic status are obtained. old with learning motivation of 0.252 and the amount of R² (Square) is 0.064 or 6.4%. So it can be concluded that there is an influence between the socio-economic status of parents on the learning motivation of students in the economics subject of class XI IIS SMAN 1 Sungai Kakap.Keyword: Socioeconomic Status, Learning Motivation